Diatom and pollen atlas dataset from the Northern Gulf of Mexico, USA - Erika Rodrigues; Kam biu Liu; Paulo Eduardo De Oliveira; Beatriz L Figueiredo; Qiang Yao (Data in Brief, 2023)
Diatom and pollen references such as atlases and identification keys are remarkably rare from the Gulf Coast region of the United States. This dataset describes modern and fossil diatom and pollen from Galveston Bay, Texas to Cedar Keys Florida, USA. An illustrated and descriptive atlas of diatom and pollen was compiled from original data to facilitate the identification of microfossil in sediments. For diatom atlas, we include light micrographs and detailed descriptions of a total of 32 diatom species, including 9 marine diatom species, 18 estuarine diatom species, and 5 freshwater diatom species. For pollen atlas, we include light micrographs and descriptions of a total of 28 pollen and non-pollen palynomorphs, including 3 mangrove taxa, 12 upland (tree and shrub) taxa, and 10 herbaceous taxa. The diatom atlas is referenced from LSU Global Change and Coastal Paleoecology Laboratory's light micrographs collection. The pollen and diatom datasets are associated with research articles by Yao et al. [1,2].